A novel INF2 mutation in a Korean family with autosomal dominant intermediate Charcot‐Marie‐Tooth disease and focal segmental glomerulosclerosis. Issue 2 (June 2014) - Park, Hyung J.; Kim, Hye J.; Hong, Young B.; Nam, Soo H.; Chung, Ki W.; Choi, Byung‐Ok
Abstract: Mutations in the inverted formin‐2 ( INF2 ) gene were recently identified in patients with autosomal dominant intermediate Charcot‐Marie‐Tooth (DI‐CMT) disease and focal segmental glomerulosclerosis (FSGS). Here, we identified a novel p.L132P INF2 mutation in a Korean family with DI‐CMT and FSGS by whole‐exome sequencing. This mutation was cosegregated with affected individuals in the family and was not found in the 300 controls. The two affected members exhibited juvenile onset sensorimotor polyneuropathy and FSGS. Nerve conduction studies showed an intermediate range of motor nerve conduction velocities. We report a novel INF2 mutation in a family with DI‐CMT and FSGS as the first case in Koreans. The INF2 mutation appears to be a major cause of CMT with FSGS.